Cenzura w okresie odwilży jako temat tabu - Woźniak-Łabieniec, Marzena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
During the political “thaw” of 1955−1956 the magazines circulated in the People’s Republic of Poland started to include themes which previously had been banned. One of those focused on the existence of censorship and its activities (Main Office of the Control of Press, Publications and Shows). Journalists wrote about books banned by the censorship, prohibited publications and black-listed writers, whose books were removed from libraries and destroyed. The situation changed in 1958 when once again writing about the existence and activities of the censorship was fobidden.